International migration and development in East Asia and the pacific (The World Bank, 2014)
The East Asia and Pacific region has an international emigrant population of over 21 million people, who remitted more than USD 90 billion to their home countries in 2010. The region also hosts more than 7 million migrant workers, mostly from other Asian countries. These migrant workers account for 20 percent or more of the labor force in economies such as Malaysia and Singapore and thus play a significant role in the economies of the labor-receiving countries. The aging of the population in many East Asian countries will create significant labor shortages leading to greater demand for migrant workers. For these reasons, international labor mobility is emerging as an important development issue in East Asia with important implications for the Bank’s mission of poverty reduction and supporting sustainable economic development in the region. In this context , this study analyzes the impact of migration on development of the region and how international migration should be managed in East Asia in a way that supports development goals while simultaneously protecting the rights of migrants. The study covers: trends in international migration in East Asia and overarching regional issues such as the links between macroeconomic management and remittances and the role of demographic trends in migration; the economic impact of migration and remittances on labor-sending countries and labor-receiving countries; the migration industry; and the policies and institutions that govern migration.